Data transfer between Cad system and RP system: a report - Abu Syukur, Syaimak; Md. Tap, Masine (Penerbit UTM Press, 2002)
Rapid Prototyping (RP) is a technology that transform a design generated in Computer Aided Design (CAD) to a 3D model parts. CAD models are usually done on a CAD system and then transported into the RP system. A good interface between the CAD and the RP system is one of the key factors of producing a good quality prototype. This paper reports on the results of an experimentation carried out to identify the problems in transferring data between a CAD system (UNIGRAPHICS) and an RP system (QUICKSLICE). Based on the experimentation’s results and analysis, a basic guideline is proposed for a safer data transfer between the CAD system (UNIGRAPHICS) and an RP system (QUICKSLICE).